The plastic crystal composite polyacrylate polymer electrolyte with a semi-interpenetrating network structure for all-solid-state LIBs. (2nd November 2022) - Zhang, Shujian; Lu, Yang; He, Kewu; Que, Lanfang; Zhao, Lei; Wang, Zhenbo
Abstract : Polymer electrolyte semi-interpenetrating network structure of lithium ion battery. Abstract : In order to overcome the tradeoff between the mechanical and electrochemical properties of polymer electrolytes, a novel semi-interpenetrating network structure is proposed. It can effectively solve the problems of low conductivity, poor interface stability, and weak mechanical strength of polymer electrolytes. Specifically, we use a plastic crystal composite polyacrylate polymer electrolyte doped with PVDF-HFP and after in situ UV curing, the polymer matrix with a semi-interpenetrating structure is formed by linear PVDF-HFP and cross-linked polyacrylate network structure (S-PCCE). A significant feature of the semi-interpenetrating network structure is the fine integration of the cross-linked polymer network and the linear polymer, resulting in synergistic effects that can improve the flexibility, mechanical strength, and ionic conductivity of the plastic-crystal composite polymer electrolyte. The ionic conductivity can reach 1.45 × 10 −3 S cm −1 at room temperature and 4.8 × 10 −3 S cm −1 at 60 °C, which is conducive to high battery performance. The LiFePO4 /S-PCCE/Li battery has an initial discharge specific capacity of 156 mA h g −1 and a maximum discharge specific capacity of 163 mA h g −1 at 0.2C. After 50 cycles, the battery can still maintain a high discharge specific capacity of 155 mA h g −1 and a Coulomb efficiency of 99.4%. At the same time, the thermogravimetric curve shows that the electrolyte has good adaptability to high temperatures. Therefore, polymer electrolytes with a semi-interpenetrating network structure have good application prospects.